Relationship Between BMI Degree and Non-Alcoholic Fatty Liver Disease Risk Factors - Marpaung, Chairunnisa Fitri; Siregar, Gontar Alamsyah; Ilhamd (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2021)
Background: Obesity is a major risk factor for cardiovascular disease, type 2 diabetes, high blood pressure, sleep apnea, psychological issues, some musculoskeletal conditions, and some cancers. The aim of the study to evaluate the correlation between BMI and risk factor of non-alcoholic fatty liver disease (NAFLD). Method: The research was conducted cross-sectionally in NAFLD patients who were treated at RSUP H Adam Malik Medan and got approval from the Ethics Commission for Health Research. Sample research is NAFLD patients who are taken in consecutive sampling that meets the criteria of inclusion and exclusion.  Body mass index (BMI) is obtained by dividing a person's weight in kilograms by their height in square meters, define obesity (OB) if BMI  >  25,  overweight  (OW) BMI  23-24.9, and normoweight (NW) BMI 18.5-22.9. Diagnose NAFLD by performing ultrasound examination, resistin and adiponectin examination with ELISA (Sandwich Immunoassay), liver function according to IFCC (International Federation of Clinical Chemistry), and albumin checked by BCG method. Result: There were 67 patients (NM=32, OW=15, OB=20) NAFLD with an average age of 42.1± 11.9 years,  Comparison of NAFLD risk factors in normoweight, overweight, and obesity, showing very significant results (all p<0.001). There is a very significant correlation between BMI and all NAFLD risk factors (all p<0.001). Conclusion: There are very significant correlates between BMI and all inflammatory factors of NAFLD.